ADSORPSI METHYLENE BLUE OLEH ARANG AKTIF: MINI REVIEW - Mulyana, Mulyana; Wirawan, Teguh; Marliana, Eva (PROSIDING SEMINAR KIMIA, 2024)
Methylene blue is a cationic dye molecule which is quite dangerous for the body, one of which can cause irritation of the digestive tract if swallowed, cause cyanosis if inhaled, and cause skin irritation if touched. Adsorption is one of the separation methods most often used in most industries, because the process is easy, and the operating costs are also relatively cheap. Activated charcoal is widely used as an adsorbent material because it has high porosity and surface area and has good absorption capacity for organic and non-organic materials. In this research, a literature study has been carried out on the adsorption of methylene blue with activated charcoal adsorbent from various types of ingredients. There are various factors that can influence the adsorption ability of methylene blue by activated carbon, such as the type of original material, the type of activator used to include HCl, NaCl, KOH, NaOH, H2SO4, and Na2CO3, as well as the temperature range for carbonation between 300-700oC. Adsorption parameters varied, such as pH between 4-9, contact time between 20-240 minutes, and adsorption capacity between 6.90-1614.968 mg/g. Keywords: Methylene blue, Adsorption, Activated charcoal.